Phosphorus sources associated with organic compound in broccoli production and soil chemical attributes - Cardoso, Antonio Ismael Inácio [UNESP]; Silva, Priscilla Nátaly de L. [UNESP]; Colombari, Lidiane F. [UNESP]; Lanna, Natália B. L. [UNESP]; Fernandes, Dirceu M. [UNESP] (FapUNIFESP (SciELO), 2019)
Phosphorus is a finite natural resource and the use of gradual-release phosphate sources, associated with an organic compound may favor a more rational use of this nutrient, since organic matter protects P from soil fixation. The aim of this study was to evaluate the effect of phosphorus sources application, associated with organic compound at planting, on single inflorescence type broccoli production and soil chemical properties at the end of the cycle. Eight treatments were evaluated, in a 4 x 2 factorial scheme, using four phosphorus sources [thermophosphate (TM), natural phosphate (NP), reactive natural phosphate (RNP) and triple superphosphate (TSP)]; in the presence (55 t ha-1) and absence of organic compound Visafértil® at planting. The experimental design was randomized blocks, with four replicates. TSP source presented higher P contents. TM source showed, in the absence of organic compound, higher pH and contents of organic matter, Ca, Mg, SB and V%. In the presence of organic compound, NP source provided higher contents of organic matter and K. The addition of organic compound increased pH and resulted in higher contents of P, K, Ca, SB, CEC and V%. The presence of organic compound favored higher productivity for the sources TM, NP and TSP. Among these sources, TSP provided the highest production both in the presence or absence of organic compound, considering that NP source was the only one which did not differ from TSP for inflorescence fresh weight and productivity, both in the presence and in the absence of organic compound. We concluded that TSP and NP are the best P sources, associated with the application of organic compound.
Fontes de fósforo associadas ao composto orgânico na produção de brócolis e atributos químicos do solo
Keywords: Brassica oleracea var. italica; Organic matter; Phosphate fertilization; Productivity